(untitled) (International Journal of Artificial Intelligence Engineering and Systems, 2026)
The convergence of artificial intelligence and cloud computing has given rise to a new class of intelligent automation platforms that dynamically orchestrate distributed resources, optimize system behavior, and reduce human intervention across the service lifecycle. This paper presents a comprehensive examination of artificial intelligence engineering as a foundational discipline for building and operating such platforms. It articulates a system-level perspective that extends beyond individual algorithms to encompass architecture, governance, infrastructure, deployment strategies, and long-term sustainability. The discussion begins by tracing the evolution from simple rule-based automation to adaptive, learning-driven service controllers embedded within cloud-native architectures. Architectural trade-offs are analyzed in depth, comparing the integration of AI components as loosely coupled microservices versus deeply embedded inference engines within platform control planes. The paper critically evaluates governance frameworks required to maintain fairness, transparency, and accountability when autonomous decision-making processes reshape resource allocation and user interactions. Deployment methodologies are explored through the lens of continuous experimentation, canary releases, and observability of model behavior in production. Robustness against data drift, adversarial inputs, and cascading failures is addressed as an engineering concern that demands rigorous testing regimes and fault isolation patterns. The study further investigates the environmental footprint of AI-augmented cloud services, proposing structural mechanisms to align automated optimization with energy proportionality and carbon-aware scheduling. Policy implications are discussed with regard to regulatory compliance, liability attribution for autonomous actions, and the socio-technical dimensions of workforce displacement and skill transformation. Throughout the analysis, the paper emphasizes systemic interconnectedness, arguing that effective AI engineering for cloud automation requires a holistic design philosophy that reconciles technical performance with ethical and operational imperatives. The conclusion synthesizes these themes and outlines a research agenda for resilient, equitable, and sustainable intelligent automation.